Investigation and experiment of radar systems in unmanned arial vehicles - Chow, Chei Yen (Nanyang Technological University, 2024)
Radar systems are one of the most complex systems as it involves many electronic systems such as radio frequency circuits, digital circuits, signal processing, data processing, image processing, antenna and wireless communications. Hence, acquired necessary background knowledge and understanding of radar system working principles are crucial before carrying out any enhancement to a radar system. This report delves into the fundamental working principles for radar system with emphasis on Synthetic Aperture Radar (SAR). The aim is to establish a comprehensive understanding of radar technology as it could facilitate future enhancement to radar system particularly for SAR. The report covers the fundamentals such as radar waveforms, frequency bands, pulse repetition interval, range resolution and doppler effect. In addition, working principle of SAR and different imaging modes of SAR are explained. Lastly, the theoretical concepts are further explored and reinforced by using MATLAB simulations software which aims to aid readers in gaining better insight of how the radar subsystems work as a whole. Topics covered in the simulations include antenna radiation pattern, array antenna configuration, range resolution and radar system under different environment settings, enabling a better understanding of SAR.